Apoptosis Modulated by Oxidative Stress and Inflammation During Obstructive Nephropathy - Manucha, Walter Ariel Fernando (2012)
Kidney apoptosis and fibrosis are an inevitable outcome of progressive chronic kidney diseases where congenital obstructive nephropathy is the primary cause of the end-stage renal disease in children, and is also a major cause of renal failure in adults. The injured tubular cells linked to interstitial macrophages, and myofibroblasts produce cytokines and growth factors that promote an inflammatory state in the kidney, induce tubular cell apoptosis, and facilitate the accumulation of extracellular matrix. Angiotensin II plays a central role in the renal fibrogenesis at a very early stage leading to a rapid progression in chronic kidney disease. The increasing levels of angiotensin II induce pro-inflammatory cytokines, NF-B activation, adhesion molecules, chemokines, growth factors, and oxidative stress. Furthermore, growing evidence reports that angiotensin II (a pro-inflammatory hormone) increases the mitochondrial oxidative stress regulating apoptosis induction. This review summarizes our understanding about possible mechanisms that contribute to apoptosis modulated by inflammation and/or oxidative stress during obstructive nephropathy. The new concept of antiinflammatory tools regulating mitochondrial oxidative stress will directly affect the inflammatory process and apoptosis. This idea could have attractive consequences in the treatment of renal and other inflammatory pathologies.